Quality Matters More Than Quantity: Parent–Child Communication and Adolescents’ Academic Performance - Zhang, Yue (Frontiers in Psychology, 2020)
This study examined the effects of parent–child communication, including the quantitative and qualitative aspects of these communications, on young American adolescents’ academic performance by using an Early Childhood Longitudinal Study-Kindergarten dataset. We considered children’s self-concept a mediator in examining the effects. Structural equation modeling was used for evaluating the model. The results revealed that the quality of parent–child communication was positively associated with these children’s academic performance, and this association can be mediated by the adolescents’ self-concept. However, the quantity of parent–child communication did not show a direct or an indirect association with the adolescents’ academic achievements. These findings suggest that efforts to improve the quality of parent–child communication and to strengthen the connection between high-quality communications and adolescents’ self-concept may benefit young adolescents’ academic development.